Предмет: Алгебра,
автор: Аноним
помогите пожалуйста
Приложения:
Ответы
Автор ответа:
1
Ответ:
-1
Объяснение:
cos(π/4+2) - cos(π/4-2) = -2 sin((π/4+2+π/4-2)/2)sin ((π/4+2-π/4+2))= -2sin(π/4)*sin4
sin(π/4+2) - sin(π/4-2) =2sin(π/4+2-π/4+2)cos(π/4+2+π/4-2)= = = -tg π/4= -1
Приложения:
Похожие вопросы
Предмет: Английский язык,
автор: btrchik34
Предмет: Русский язык,
автор: Starfire21
Предмет: Русский язык,
автор: avtorzn62
Предмет: Русский язык,
автор: seniormuxammad
Предмет: Русский язык,
автор: Nurana3111